EFEKTIVITAS PENGGUNAAN MEDIA ULAR TANGGA TERHADAP PEMAHAMAN PESERTA DIDIK MATERI OPERASI PECAHAN - Kurnia Miftahul Faizah; Ema Butsi Prihastari; Elinda Rizkasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The board game “Snakes and Ladders” has been explored as a learning tool to help fourth-grade students at SD Kestalan, Surakarta, better understand fraction operations during the 2024–2025 academic year. This study employed a quantitative approach with a pre-experimental One Group Pre-test and Post-test design, involving 25 students selected through saturated sampling. Data were collected using tests, observations, and documentation, then analyzed with the Shapiro-Wilk normality test, paired-sample t-test, and N-Gain calculation. The results revealed a significant improvement in students’ understanding, with the average score increasing from 58.00 in the pre-test to 79.20 in the post-test. The paired-sample t-test confirmed a significant difference between pre-test and post-test scores (significance = 0.000 < 0.05; t = -18.196). The effectiveness of the game was also supported by an N-Gain value of 0.612 (61.20%). These findings suggest that educational games like Snakes and Ladders can make learning more engaging and enjoyable while enhancing motivation and conceptual understanding. Such media offer a creative alternative for teachers to teach fractions, turning lessons into interactive and meaningful experiences.